ChemInform Abstract: Reaction of 7‐Phenyl‐7H‐pyrazolo[3, 4‐d][1, 2, 3]triazin‐4‐ol with Thionyl Chloride. Issue 12 (25th March 2014) - Khutova, B. M.; Klyuchko, S. V.; Gurenko, A. O.; Vasilenko, A. N.; Rusanov, E. B.; Brovarets, V. S.
Abstract Depending on reaction conditions, different pyrazole derivatives are synthesized.